Deep brain stimulation versus ablative surgery for treatment‐refractory obsessive‐compulsive disorder: A meta‐analysis. (11th February 2021) - Hageman, Sarah Babette; van Rooijen, Geeske; Bergfeld, Isidoor O.; Schirmbeck, Frederike; de Koning, Pelle; Schuurman, P. Rick; Denys, Damiaan
Abstract: Objective: Ablative surgery (ABL) and deep brain stimulation (DBS) are last‐resort treatment options for patients suffering from treatment‐refractory obsessive‐compulsive disorder (OCD). The aim of this study was to conduct an updated meta‐analysis comparing the clinical outcomes of the ablative procedures capsulotomy and cingulotomy and deep brain stimulation. Methods: We conducted a PubMed search to identify all clinical trials on capsulotomy, cingulotomy, and DBS. Random effects meta‐analyses were performed on 38 articles with a primary focus on efficacy in reducing OCD symptoms as measured by a reduction in the Yale‐Brown Obsessive‐Compulsive Scale (Y‐BOCS) score and the responder rate (≥35% reduction in Y‐BOCS score). Results: With responder rates of 48% and 53% after 12–16 months and 56% and 57% at last follow‐up for ABL and DBS, respectively, and large effect sizes in the reduction in Y‐BOCS scores, both surgical modalities show effectiveness in treating refractory OCD. Meta‐regression did not show a statistically significant difference between ABL and DBS regarding these outcomes. Regarding adverse events, a statistically significant higher rate of impulsivity is reported in studies on DBS. Conclusion: This meta‐analysis shows equal efficacy of ABL and DBS in the treatment of refractory OCD. For now, the choice of intervention should, therefore, rely on factors such as risk of developing impulsivity, patient preferences, and experiences of psychiatrist and neurosurgeon. Future research should provide more insight regarding differences between ABL and DBS and response prediction following direct comparisons between the surgical modalities, to enable personalized and legitimate choices between ABL and DBS.